2018
DOI: 10.1016/j.pmrj.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wheelchair Stroke Pattern on Upper Extremity Muscle Fatigue

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…8,9 There are several studies on which stroke patterns are more appropriate to prevent soft tissue injuries of the upper limb. [8][9][10] The Clinical Practice Guideline for Preserving Upper Limb Function Following Spinal Cord Injury 11 suggested the use of SC pattern, which had less angular joint velocity and lower cadence. [8][9][10][11][12] A more recent study demonstrated that the SC pattern appeared to be more fatiguing to shoulder muscles than the arcing pattern.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,9 There are several studies on which stroke patterns are more appropriate to prevent soft tissue injuries of the upper limb. [8][9][10] The Clinical Practice Guideline for Preserving Upper Limb Function Following Spinal Cord Injury 11 suggested the use of SC pattern, which had less angular joint velocity and lower cadence. [8][9][10][11][12] A more recent study demonstrated that the SC pattern appeared to be more fatiguing to shoulder muscles than the arcing pattern.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] A more recent study demonstrated that the SC pattern appeared to be more fatiguing to shoulder muscles than the arcing pattern. 10 It was also reported that the arcing pattern was more appropriate for uphill propulsion 13 and metabolically more effective than the SC pattern. 14 A study provides preliminary knowledge about the possible intercourse between changes in wheelchair propulsion technique and shoulder load.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations